2021
DOI: 10.24018/ejbmr.2021.6.4.763
|View full text |Cite
|
Sign up to set email alerts
|

Economic Development, Political and Socio-Political Violence Crisis in the Sub-Saharan Africa: An Economic Panel Study

Abstract: Social and political instability threatens the economic and social development of nations. Political persecution is therefore characterized by socio-political instability as a barrier to development that creates economic difficulties, limited public and private investments and hinders national development. This article describes political persecution and economic development through a close examination of the African ministry which covers key issues such as welfare and drug trafficking. We use various measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In contrast to that linking of economic performance to political stability, collection of empirical evidence on the determinants of political instability has not been less de rigueur in developmental literature. Analyzing data drawn from a cross-section of Colombian provinces between 2000 and 2014, using a methodology later mimicked by Addy et al. (2021), Poveda and Carvajal (2019) likewise demonstrated that skewed distribution of wealth (captured by GINI coefficients), narcotics trading, high unemployment rates and displacement of population generate violence.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to that linking of economic performance to political stability, collection of empirical evidence on the determinants of political instability has not been less de rigueur in developmental literature. Analyzing data drawn from a cross-section of Colombian provinces between 2000 and 2014, using a methodology later mimicked by Addy et al. (2021), Poveda and Carvajal (2019) likewise demonstrated that skewed distribution of wealth (captured by GINI coefficients), narcotics trading, high unemployment rates and displacement of population generate violence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Notwithstanding that the predominant focus of the literature in political economy and development is on how political instability adversely affects the economic performance of a country (Fosu, 2003;Aisen and Veiga, 2006), several studies clearly link economic conditions as a salient causal factor of political instability: the more abject the former, the greater the scale of the latter (Aisen and Veiga, 2011). In Addy et al (2021), informed by the crisis management strategic approach of Driscoll and Kraay, the main thrust of the research focused on analyzing how political persecution could retard economic and social development in a cross-section of countries of SSA over the period 2000-2014. In passing, however, these scholars, using a GMM methodology for parametric estimation, linked skewed distribution of wealth (captured by GINI coefficients), illegal narcotics usage, high unemployment rates and homelessness to violence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is ample evidence at a global level that there is an inverse relationship between crime and economic growth; for example, Mocetti and Rizzica (2021) and Bernardo et al (2021) provide evidence for the Italian economy, Santos-Marquez (2021) offers evidence in the Colombian case. Addy et al (2021) also document an inverse relationship between crime and economic growth and development, using panel data modelling for a sample of Sub-Saharan African countries. Nayebyazdi (2017) studies the relationship between criminal activity and economic growth in 27 member countries of the European Union.…”
Section: Literature Reviewmentioning
confidence: 95%